Enabling team learning in healthcare. (3rd May 2016) - Boak, George
ABSTRACT: This paper is based on a study of learning processes within 35 healthcare therapy teams that took action to improve their services. The published research on team learning is introduced, and the paper suggests it is an activity that has similarities with action research and with those forms of action learning where teams address collective problems to enhance organisational performance. The paper proposes factors within the teams and in the teams' environments that enabled team learning, in particular, within the team, the behaviours of team leaders to encourage learning, communication, planning, action and review, and in the teams' environments, the behaviour of senior managers and other stakeholders in positions of authority, access to effective information systems, and the availability of a modest amount of resource to enable team learning.